2021
DOI: 10.1287/mnsc.2020.3826
|View full text |Cite
|
Sign up to set email alerts
|

“Stiff Business Headwinds and Uncharted Economic Waters”: The Use of Euphemisms in Earnings Conference Calls

Abstract: This paper studies whether euphemisms obfuscate the content of earnings conference calls and cause investors to underreact. I argue that managers’ use of euphemisms can alleviate the impact of bad news and delay the market reaction to adverse information. Using a dictionary of corporate euphemisms, I find that their use by managers—but not by analysts—is negatively associated with both immediate and future abnormal returns, and their frequency moderates the negative market reaction to bad earnings news. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Whereas several papers relate the tone of IPO prospectuses to information production costs and IPO underpricing (e.g., Ferris et al, 2013;Loughran & McDonald, 2013), we examine the information content of the tone of SEO prospectuses. Our findings indicate that cautionary tone of SEO filings has negative information content that is gradually incorporated into the issuers' stock prices, in line with the findings in non-SEO settings by Tetlock et al (2008), Li (2006Li ( , 2010aLi ( , 2010b, Agarwal et al (2016), Ertugrul et al (2017), Cohen et al (2020), and Suslava (2021.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Whereas several papers relate the tone of IPO prospectuses to information production costs and IPO underpricing (e.g., Ferris et al, 2013;Loughran & McDonald, 2013), we examine the information content of the tone of SEO prospectuses. Our findings indicate that cautionary tone of SEO filings has negative information content that is gradually incorporated into the issuers' stock prices, in line with the findings in non-SEO settings by Tetlock et al (2008), Li (2006Li ( , 2010aLi ( , 2010b, Agarwal et al (2016), Ertugrul et al (2017), Cohen et al (2020), and Suslava (2021.…”
supporting
confidence: 85%
“…Cohen et al (2020) show that textual changes of financial reports, especially changes indicating negative sentiment and changes in the "Risk Factors" section, are negatively related to future stock returns, suggesting that investors are inattentive and only gradually uncover the information content of the textual changes. Suslava (2021) finds that managers' use of euphemisms (indirect words or phrases to refer to something unpleasant) in earnings conference calls is negatively related to both immediate and future abnormal stock returns. Consistent with the tenor of the findings in these papers, we find that more cautionary tone in SEO prospectus filings is related to higher offer price discounts and/or followed by more negative stock returns.…”
mentioning
confidence: 99%
“…For example, when CEOs speak in more vague terms (e.g., using words such as "approximately", "probably," and "maybe"), analysts report greater uncertainty and lower positive reactions (Dzieliński, Wagner, & Zeckhauser, 2017). On the positive side, research found that when CEOs used euphemistic language (e.g., "a bump in the road"; "caught by surprise"; "in uncharted waters"), this mitigated the effects of bad news announcements on stock market returns (Suslava, 2021). Overall, these findings suggest that how CEOs discuss about business matters for how analysts evaluate their companies and, ultimately, how CEOs' companies fare on the stock market.…”
Section: Introductionmentioning
confidence: 91%
“…13 This suggests that CEOs might have been reluctant to address the crisis in calls with financial analysts since raising such "bad news" in conference calls could undermine analyst and investor confidence and adversely influence stock price (Feldman, 1996). Indeed, research suggests that CEOs try to avoid bringing bad news during conference calls (Hollander, Pronk, & Roelofsten, 2010) or try to strategically minimize it (Suslava, 2021). Future research should explore CEO decision-making regarding whether and how to bring up the more human aspects of a crisis in conference calls with financial analysts.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…NLP studies in accounting use three main methods to extract textual disclosures from corporate filings. Under the dictionary method, researchers count the number of positive/negative words (Feldman, Govindaraj, Livnat, and Segal 2010;Loughran and McDonald 2011), certain idioms (Klevak, Livnat, and Suslava 2019;Suslava 2021), or business keywords (Henry 2006).…”
Section: Extraction Of Textual Characteristics Of Cam Disclosuresmentioning
confidence: 99%